MDM2 SNP309 accelerates tumor formation in a gender-specific and hormone-dependent manner. - Bond, G; Hirshfield, K; Kirchhoff, T; Alexe, G; Bond, E; Robins, H; Bartel, F; Taubert, H; Wuerl, P; Hait, W; Toppmeyer, D; Offit, K; et al. (2006)
The importance of the p53 stress response pathway in the suppression of tumor formation is well documented. In a previous report, a single nucleotide polymorphism (SNP309 T/G) was found in the promoter of the MDM2 gene resulting in higher levels of MDM2 RNA and protein and, consequently, in the attenuation of the p53 pathway both in vitro and in vivo. As the SNP309 locus is found in a region of the MDM2 promoter, which is regulated by hormonal signaling pathways, and the G-allele of SNP309 increases the affinity of a well-described cotranscriptional activator of nuclear hormone receptors (i.e., Sp1), the hypothesis that the SNP309 locus could alter the effects of hormones on tumorigenesis was tested in vivo in humans. Data obtained from patients with three different sporadic cancers, from four independent case studies, support this hypothesis, providing an example for the genetic basis of gender differences in cancer and showing that the genotype at a specific locus can affect how hormones, like estrogen, affect tumorigenesis in humans.